PENGEMBANGAN E-LKPD BERBASIS INKUIRI TERBIMBING UNTUK MENINGKATKAN KAMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI IKATAN KIMIA - Anggita Pratiwi Nasution; Ani Sutiani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to produce a product in the form of a valid, practical, and effective guided inquiry-based electronic learner worksheet (E-LKPD) to improve students' critical thinking skills on chemical bonding materials. This research and development is designed based on the stages of the 4-D development model that is adapted to 3-D, including the define, design, and develop stages. The sample in this study is 32 students in class X-4 MAN 1 Medan. Based on the results of the study, the validity of the E-LKPD developed obtained an average percentage of assessment of 93% by experts with very valid qualifications. Through the E-LKPD practicality questionnaire by teachers and students, an average percentage of assessment of 85.4% by teachers and 90.4% by students with qualifications classified as very practical to be used in the learning process was obtained. The implementation of learning with the application of E-LKPD based on guided inquiry has been carried out to see the effectiveness of E-LKPD with a set assessment reference, namely for completeness based on the gain analysis obtained from pretest and posttest scores to see the improvement of students' critical thinking skills in chemical bond materials, the results were obtained that students' critical thinking skills have increased with an average gain score of 0.70. This means that the increase is in the high category. Based on the data obtained from the research, it is concluded that the guided inquiry-based E-LKPD developed in this study has met the valid, practical, and effective qualifications.